2017
DOI: 10.1039/c6mb00653a
|View full text |Cite
|
Sign up to set email alerts
|

Integrating multiple omics data for the discovery of potential Beclin-1 interactions in breast cancer

Abstract: Breast cancer has been reported as one of the most frequently diagnosed malignant diseases and the leading cause of cancer death in women all around the world. Furthermore, this complicated cancer is divided into multiple subtypes which present different clinical symptoms and need correspondingly directed therapy. We took BECN1, a core gene in autophagy performing a tumor inhibitory effect, as a starting point. The study in this paper aims to identify genes related to breast cancer and its multiple subtypes by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…As a specific marker of autophagy, Beclin-1 has been the focus of previous research. Recent studies have reported that Beclin-1 is downregulated in glioblastoma, liver cancer, bladder cancer and breast cancer (15)(16)(17)(18), while it is upregulated in colon cancer (19). The present study revealed that Beclin-1 expression was downregulated in NSCLC tissues, consistent with a study by Zheng et al (20), which demonstrated that the regulation of Beclin-1 may serve a role in the development of this type of cancer.…”
Section: Discussionsupporting
confidence: 91%
“…As a specific marker of autophagy, Beclin-1 has been the focus of previous research. Recent studies have reported that Beclin-1 is downregulated in glioblastoma, liver cancer, bladder cancer and breast cancer (15)(16)(17)(18), while it is upregulated in colon cancer (19). The present study revealed that Beclin-1 expression was downregulated in NSCLC tissues, consistent with a study by Zheng et al (20), which demonstrated that the regulation of Beclin-1 may serve a role in the development of this type of cancer.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, various other studies have profiled the global proteomic changes in response to artificial impairment of autophagy by knocking out critical autophagy genes (Avin-Wittenberg et al, 2015;Mathew et al, 2014). Studies combining different -omic readouts have also been performed in various contexts to understand the role of autophagy in various processes and phenotypes (Chen et al, 2017;Kramer et al, 2017;Masclaux-Daubresse et al, 2014;Stingele et al, 2012). However, the studies aforementioned do not provide an explanation as to how the proteome level alterations are indeed dependent on autophagy from a mechanistic point of view.…”
Section: Discussionmentioning
confidence: 99%
“…They used the Least Absolute Shrinkage and Selection Operator (LASSO) method which is designed for -omics data integration. By bringing together three different data types namely mRNA expression (DNA microarray), DNA methylation (Illumina Methylation Assay), and copy number alteration (GenomeWideSNP_6 array) data provided by The Cancer Genome Atlas database (TGCA— https://cancergenome.nih.gov/ ), they identified the regulators of BECN1, a core autophagy component, which has an inhibitory effect on tumor formation (Chen et al, 2017 ).…”
Section: Integration Of Omics Dataset To Understand Autophagy Bettermentioning
confidence: 99%